(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Antibiotic resistance is serious global problem. Many commercial antibiotics due to over use have induced some microbes to become multi drug resistant. Tetracyclines are important bactericidal agents towards various bacteria. Resistance towards tetracyclines includes factors like intrinsic, adaptive & mutational modes. Thereby many researchers are gravitating towards searching for novel anti-microbial agents from the natural world. In this paper, the resistance towards tetracyclines have been briefly stressed upon along with the evaluation of the anti-microbial role of Chickpea (Cicer arietinum) towards a set of bacteria. Bacteria, Klebseilla & Bacillus subtilis were grown as a lawn culture that was then exposed to varying concentrations of butanolic & aqueous extracts. After 24 hours, the butanolic extract showed higher activity as compared to the aqueous extracts. However, Sumycin showed the highest activity. This result has given hope that novel anti-microbial agents can be isolated from this plant.